Social Action in Tongkling Performing ART - Winata, Dean Arda; Utomo, Udi; Sumaryanto Florentinus, Totok (Catharsis, 2019)
Tongkling is a traditional music from Glodogan village, Bawen District, Semarang Regency. Tongkling is always invited to take part in Merti Dusun and Kirab Budaya events in Semarang regency. The purpose of this research is to analyze the form of performance and social action in Tongkling art. The method used in this research was qualitative with sociological approach. The technique of data collection were observation, interview, and document study. The technique of data validity used triangulation technique and data analysis technique that follow interactive model analysis stages. The research results show that the form of Tongkling art presentation are divided into traditional and electric types. The traditional types is presented during carnival while electric types is presented on the stage. The social action of the society is also developing, the beginning was for patrolling, and nowadays, this art is for enliven Kirab Budaya and Merti Dusun evenst in Semarang Regency. The research implication of Tongkling Ortega for the society in Glodogan village is for social interaction and for preserving the existence of Tongkling in traditional events. Tongkling Ortega art increases the art treasury in Semarang Regency.